Liquid dispersions and powders of cerium-based core-shell particles, methods for producing same and their use in polishing
Patent Information
- Application Number
- JP2023570448
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-17
- Filing Date
- 2022-05-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-05-17
AI Technical Summary
Existing cerium-based polishing compositions for chemical mechanical polishing (CMP) face challenges in achieving high material removal rates with low defects, often due to inappropriate particle sizes and stability issues, which affect their abrasive capabilities and substrate quality.
The development of cerium-based core-shell particles with a rough surface morphology, produced through a method involving controlled temperature and pH conditions, enhances polishing properties by increasing surface roughness and maintaining particle size distribution, ensuring nanoparticles remain attached to the core during polishing.
The core-shell particles exhibit improved polishing performance with higher removal rates and reduced defects, maintaining particle stability and effectiveness in CMP processes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to European Patent Application No. 21174022.0, filed May 17, 2021, the entire contents of which are incorporated herein by reference for all purposes.
[0002] The present invention relates to a process for producing dispersions of cerium-based core-shell particles, to the dispersions and powders obtainable by such a process, and to their uses in the field of polishing, in particular chemical-mechanical polishing. [Background technology]
[0003] Ceric oxide is generally used for polishing applications, especially chemical mechanical polishing. The development of the electronics industry increasingly requires the use of compositions for polishing various workpieces, such as disks or dielectric compounds. These compositions, generally in the form of dispersions, must exhibit a certain number of properties. For example, they must provide a high degree of material removal, which reflects their polishing ability. They must also have as low a defectivity as possible, the term "defectivity" being intended to mean in particular the amount of scratches exhibited by a substrate once treated with the composition. For reasons of stability and ease of use, these dispersions must contain particles of submicron dimensions, i.e. generally less than 300 nm. The presence of too fine particles in these dispersions reduces the polishing ability of the particles, while too large particles can contribute to an increase in defects.
[0004] In this regard, we believe that there is a need for cerium-based particles that have improved polishing properties when used in chemical mechanical polishing processes, as well as methods for their manufacture that are simple and easy to implement on an industrial scale. Summary of the Invention
[0005] These problems are solved by the present invention, which provides inter alia novel cerium-based particles having a rough surface due to their particular core-shell morphology and method of manufacture.
[0006] Therefore, one object of the present invention is to (a) providing an aqueous dispersion comprising particles of cerium oxide optionally doped with at least one metal (M); providing an aqueous solution comprising a cerium (III) salt; providing an aqueous peroxygen solution; and optionally providing an aqueous solution comprising at least one metal (M') salt; (b) contacting the aqueous dispersion with the aqueous solution provided in step (a) while maintaining a temperature comprised between 0° C. and 80° C. and a pH not greater than 11 to produce a dispersion of cerium-based core-shell particles; The present invention relates to a method for producing a dispersion of cerium-based core-shell particles in a liquid, comprising: At least one of steps (a) or (b) is carried out in the presence of nitrate ions.
[0007] The present invention also relates to cerium-based core-shell particles and dispersions thereof obtainable or obtainable by this process.
[0008] The cerium-based core-shell particles of the present invention can be described as a core particle of cerium oxide optionally doped with at least one metal (M) and a shell consisting of a plurality of nanoparticles of cerium oxide optionally doped with at least one metal (M'), said nanoparticles being formed on the surface of the core particle, the ratio of the average particle size of the core-shell particles as measured by TEM to the average particle size of the core-shell particles as measured by BET being at least 1.5.
[0009] Advantageously, the specific core-shell morphology of the particles of the invention increases their surface roughness and therefore their specific surface area, compared to the smooth cerium oxide particles without a shell according to the invention. Thus, by increasing the contact surface between the particle and the substrate to be polished, the polishing properties of the core-shell particles of the invention are improved, making it possible to advantageously use them in chemical mechanical polishing processes. The core-shell particle dispersions of the invention in particular allow a higher removal rate due to their rough surface while maintaining the same defects, due to the comparable particle size distribution, compared to the dispersions of smooth surface cerium oxide particles without a shell according to the invention.
[0010] As described in more detail herein below, the cerium-based core-shell particle dispersions of the present invention can be used to prepare powders of cerium-based core-shell particles, as well as polishing compositions.
[0011] Moreover, one advantage of the core-shell particles of the present invention is that the nanoparticles from the shell are well attached to the core particles. It has been particularly observed that they remain attached to the core during the entire chemical mechanical polishing process carried out. This is all the more important because the particle shell bears the mechanical stress during the chemical mechanical polishing process. If the nanoparticles of the shell are dislodged during polishing, these small cerium oxide particles may remain attached to the substrate even after the cleaning process, which is not acceptable to the end user. This would result in loss of substrates and unacceptable costs for frequent polishing composition replenishment.
[0012] Another advantage of the core-shell particles of the present invention lies in the fact that they have a suitable size range for CMP applications and are monodisperse. [Brief description of the drawings]
[0013] [Figure 1] 1 is a TEM image of a dispersion of core-shell particles of the invention having a cerium oxide core and a cerium oxide shell, obtained by the method described in Example 1. [Diagram 2]1 is an SEM image of a dispersion of cerium oxide particles intended to be used as core particles in the method described in Example 1. [Diagram 3] 4 is a TEM image of a dispersion of core-shell particles of the invention obtained by the method described in Example 2, having a lanthanum-doped cerium oxide core and a cerium oxide shell. [Figure 4] 4 is a TEM image of a dispersion of core-shell particles of the invention obtained by the method described in Example 3, having a cerium oxide core and a lanthanum-doped cerium oxide shell.
[0014] Transmission electron microscope (TEM) images were collected using a JEM-1400 (JEOL) instrument operating at 120 kV. Scanning electron microscope (SEM) images were obtained using a SEMS-5500 instrument from Hitachi High Technologies Corporation.
[0015] definition In the present disclosure, the expression "comprises" should be understood to mean "comprises at least one."
[0016] When referring to the aqueous dispersions or solutions provided in steps (a) and (b) of the process of the present invention, the expression "comprising" encompasses embodiments in which said dispersions and solutions "consist of" the compounds described in that connection.
[0017] The expression "included in" must be understood as including the limiting values.
[0018] In the entire description, the term "cerium-based" includes cerium oxide and metal-doped cerium oxide. Cerium oxide generally has a purity of at least 99.8% by weight based on the weight of the oxide. Cerium oxide is generally a crystalline ceric oxide. The term "cerium oxide doped with at least one metal" means that the metal ions partially replace the cerium ions in the CeO2 lattice. It therefore also means a mixed oxide of cerium and at least one metal. It may also mean, in some embodiments, a solid solution. In that case, the metal atoms are fully diffused in the cerium oxide crystal structure. Some impurities other than the metal may be present in the oxide. The impurities may come from the raw materials or starting materials used in the preparation process of the metal-doped oxide. The total percentage of impurities is usually less than 0.2% by weight based on the weight of the metal-doped oxide. Residual nitrates are not considered as impurities in this application.
[0019] The expression "dispersion" in reference to a dispersion of cerium-based particles means a system of solid particulates of submicron size stably dispersed in a liquid medium, said particles optionally containing residual amounts of bound or adsorbed ions, e.g., nitrate or ammonium.
[0020] The term "nanoparticles" in relation to the small particles forming the shell of the core-shell particle of the invention means that these small particles have an average size comprised between 1 and 100 nm, which can be determined, inter alia, by TEM as explained below.
[0021] Different parameters can be used to characterize the particle size and particle size distribution: - the entire core-shell particle of the invention; - in particular by characterizing the particles provided in the dispersion of step (a) of the method of the invention, the core particles; - Nanoparticles from the shell.
[0022] In relation to particle dispersions: - the average particle size of n (>100) particles can be determined using photographs of their dispersions obtained by transmission electron microscopy (TEM); - The standard deviation referred to in this application is also determined by the TEM method. It has its usual mathematical meaning. It is the square root of the variance and is given by the formula:
number
number
[0023] For particles in powder form (dry particles): The average particle size of the particles can be determined by X-ray diffraction (XRD) techniques. The value measured by XRD corresponds to the size of the coherent range calculated based on the width of the two most intense diffraction lines and using the Scherrer model. - The specific surface area can be determined on a powder by adsorption of nitrogen by the Brunauer-Emmett-Teller method (BET method). This method is disclosed in the standard ASTM D 3663-03 (reapproved in 2015). This method is also described in the periodical "The Journal of the American Chemical Society, 60, 309 (1938)". The specific surface area can be measured automatically on an instrument TriStar 3000 from Micromeritics according to the manufacturer's guidelines. Before the measurement, the sample in powder form shall be degassed under static air by heating at a temperature of at most 210 °C in order to remove the adsorbed species. - The average particle size estimated by BET is the theoretical average particle size of the particles obtained from the specific surface area measured by the BET method, assuming that the particles are non-porous spherical particles of cerium oxide with a density of 7.2.
[0024] The size distribution of particles can be characterized by various parameters, which are based on volumetric and non-number distribution: - The hydrodynamic mean diameter Dh, which is equal to the median diameter D50 of the particles, can be determined by dynamic light scattering (DLS). This technique allows the measurement of the hydrodynamic mean diameter Dh of solid objects, whose value is affected by the presence of particle agglomerates. Measurements are therefore usually carried out on dispersions of particles in water. Dh is determined using an instrument Zetasizer Nano-ZS from Malvern, following the manufacturer's guidelines. The sample usually needs to be diluted in deionized water. A dilution factor of 30,000 can be applied; - Laser diffraction can also be used to measure the size distribution of particles. A laser particle sizer such as the Horiba LA-910 can be used according to the manufacturer's guidelines. For the measurements, a relative refractive index of 1.7 can be used. From the volume distribution obtained by laser diffraction, various parameters commonly used in statistics can be estimated, such as D10, D50, D90 and the dispersion index.
[0025] D10 is the diameter determined from a distribution obtained by laser diffraction, where 10% of the particles have a diameter smaller than D10.
[0026] D50 is the median diameter measured from a distribution obtained by laser diffraction.
[0027] D90 is the diameter determined from a distribution obtained by laser diffraction, where 90% of the particles have a diameter smaller than D90.
[0028] "Dispersion index" is defined by the following formula: σ / m=(D90-D10) / 2D50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention relates to (a) providing an aqueous dispersion comprising particles of cerium oxide optionally doped with at least one metal (M); providing an aqueous solution comprising a cerium (III) salt; providing an aqueous peroxygen solution; and optionally providing an aqueous solution comprising at least one metal (M') salt; (b) contacting the aqueous dispersion with the aqueous solution provided in step (a) while maintaining a temperature comprised between 0° C. and 80° C. and a pH not greater than 11 to produce a dispersion of cerium-based core-shell particles; The present invention relates to a method for producing a dispersion of cerium-based core-shell particles in a liquid, preferably water, comprising: At least one of steps (a) or (b) is carried out in the presence of nitrate ions.
[0030] The aqueous dispersion provided in step (a) Particles of cerium oxide, optionally doped with at least one metal (M), are provided to serve as core particles for the cerium-based core-shell particles produced by the process of the present invention.
[0031] In the following detailed description of step (a), these particles will be referred to as "cerium-based particles" unless otherwise specified.
[0032] The starting dispersion used in step (a) can be prepared by dispersing a commercially available powder of cerium-based particles in water. Alternatively, commercially available dispersions of cerium-based particles can be used. If necessary, these dispersions can be concentrated or diluted and / or transferred from their original organic phase into water to carry out step (a) by methods known per se.
[0033] The dispersion used in step (a) can contain at least 3% by weight, in particular at least 5% by weight, at least 10% by weight, at least 15% by weight, and even more particularly at least 20% by weight of cerium-based particles, based on the total weight of the dispersion. The yield of the reaction is further improved. The dispersion used in step (a) can contain less than 50% by weight, in particular less than 40% by weight, and more particularly less than 35% by weight of cerium-based particles, based on the total weight of the dispersion.
[0034] According to one embodiment, the cerium-based particles used in step (a) are cerium oxide particles, in particular ceria particles. Such particles can be advantageously produced by one of the methods described by the applicant in WO 2008 / 043703, WO 2010 / 020466 and WO 2015 / 091495.
[0035] Such cerium oxide particles (and therefore core particles) may exhibit: - an average particle size of at most 250 nm, in particular at most 200 nm, more particularly at most 170 nm, measured by TEM; an average particle size of at least 30 nm, in particular at least 40 nm, more particularly at least 50 nm, measured by TEM. The standard deviation of said average particle size values may be at most 30%, in particular at most 20%, more particularly at most 15%; and / or - an average particle size of at most 120 nm, in particular at most 110 nm, calculated from BET surface measurements; an average particle size of at least 15 nm, in particular at least 19 nm, in particular at least 30 nm, in particular at least 40 nm, calculated from BET surface measurements; and / or a median diameter D50, determined from a distribution obtained by laser diffraction, comprised between 60 nm and 170 nm, in particular between 70 nm and 160 nm, more particularly between 80 nm and 150 nm, and even more particularly between 90 nm and 150 nm, and / or - a dispersion index determined from the distribution obtained by laser diffraction of at most 0.5, in particular at most 0.4, more particularly at most 0.3.
[0036] According to another embodiment, the cerium-based particles used in step (a) are cerium oxide particles doped with at least one metal (M). Such particles can advantageously be produced by one of the methods described by the Applicant in WO 2015 / 197656 and WO 2018 / 229005.
[0037] According to this embodiment, said metal (M) may more particularly be selected from the group consisting of alkali metal elements, alkaline earth metal elements, rare earth elements, actinide elements, transition metal elements and post-transition metal elements from the periodic table.
[0038] The expression "rare earth" is understood to mean an element from the group consisting of yttrium and the elements of the periodic table having atomic numbers from 57 to 71 inclusive. A transition metal element is defined as any element of the d-block of the periodic table, including groups 3 to 12 of the periodic table. The post-transition metal elements, also known as poor metals, are defined as metallic elements of the p-block of the periodic table, among others aluminium, gallium, indium, thallium, tin, lead, bismuth and polonium.
[0039] Preferably, the at least one metal (M) is selected from the group consisting of transition metal elements such as Zr; post-transition metal elements such as Al; rare earth elements such as La, Pr, Nd and Y; and alkaline earth metal elements such as Sr. More preferably, the at least one metal (M) is selected from the group consisting of lanthanum, praseodymium, neodymium and zirconium. Even more preferably, the at least one metal (M) is selected from the group consisting of lanthanum, praseodymium and neodymium. Even more preferably, the at least one metal (M) is lanthanum.
[0040] Further according to this embodiment, the molar ratio M / M+Ce in the metal (M)-doped cerium oxide particles used in step (a) may be comprised between 0.01 and 0.15, more particularly between 0.01 and 0.13, in particular between 0.01 and 0.12.
[0041] Such metal (M) doped cerium oxide particles can exhibit: - an average particle size of at most 250 nm, in particular at most 200 nm, more particularly at most 170 nm, measured by TEM; an average particle size of at least 30 nm, in particular at least 40 nm, more particularly at least 50 nm, measured by TEM. The standard deviation of said average particle size values may be at most 30%, in particular at most 20%, more particularly at most 15%; and / or - an average particle size calculated from BET surface measurements of at most 120 nm, in particular at most 110 nm; an average particle size calculated from BET surface measurements of at least 15 nm, in particular at least 19 nm, at least 30 nm, in particular at least 40 nm; and / or a median diameter D50, determined from a distribution obtained by laser diffraction, comprised between 60 nm and 700 nm, in particular between 70 nm and 200 nm; and / or - a dispersion index of at most 0.6, in particular at most 0.4, more particularly at most 0.3, determined from a distribution obtained by laser diffraction.
[0042] According to one subembodiment, the cerium-based particles used in step (a) are lanthanum-doped cerium oxide particles. Such particles may exhibit: a mean hydrodynamic diameter Dh, determined by the distribution obtained by DLS, comprised between 100 nm and 1000 nm, more particularly between 100 nm and 500 nm, even more particularly between 100 nm and 250 nm, even more particularly between 150 nm and 250 nm, and / or a median diameter D50 determined from a distribution obtained by laser diffraction, comprised between 100 nm and 700 nm, in particular between 100 nm and 200 nm, and / or - a dispersion index of at most 0.6, in particular at most 0.4, more particularly at most 0.3, determined from a distribution obtained by laser diffraction.
[0043] Such particles can in particular be produced as described in WO 2018 / 229005.
[0044] The temperature of the dispersion of cerium-based particles provided in step (a) may be set before step (b) to a value comprised between 0°C and 80°C, preferably between 10°C and 60°C, more preferably between 15°C and 45°C, in particular between 20°C and 40°C, more specifically between 25°C and 35°C, and even more specifically between 30°C and 35°C. It is preferable to set the required temperature while stirring the dispersion. Stirring can be started before adjusting the temperature.
[0045] Similarly, the pH of the dispersion of cerium-based particles provided in step (a) may be set before step (b) to a value below 11, preferably comprised between 3 and 11, preferably between 4 and 11, preferably between 8 and 11, more preferably between 8 and 10, in particular between 8 and 9, more particularly about 9. A pH adjuster may be used in that respect. Depending on the initial pH of the dispersion, the pH adjuster may be an acid or a base. Suitable acids may include nitric acid, hydrochloric acid, sulfonic acid, carbonic acid, picolinic acid, propionic acid, and mixtures thereof, preferably nitric acid. Suitable bases may include alkali metal and alkaline earth metal hydroxides as well as aqueous ammonia. Secondary, tertiary or quaternary amines may also be used. Aqueous ammonia is preferred. According to a preferred embodiment, the pH adjuster is a base, preferably aqueous ammonia.
[0046] Preparation of the core particles provided in step (a) According to one embodiment, the cerium-based particles used in step (a) are prepared by a method based on the precipitation of cerium(III) and cerium(IV) salts, comprising the following steps: (a') In an inert atmosphere, an aqueous solution of base and NO3 -with an aqueous solution comprising Ce(III), Ce(IV) and optionally at least one metal (M); (b') heat treating the mixture obtained in step (a') under an inert atmosphere; (c') the mixture obtained at the end of step (b') may optionally be acidified; (d') the solid material obtained at the end of step (b') or step (c') may optionally be washed with water; (e') The solid material obtained at the end of step (d') may optionally be subjected to a mechanical treatment to deagglomerate the particles.
[0047] The Ce(IV) / total Ce molar ratio in step (a') can be comprised between 1 / 500000 and 1 / 4000. It may usually be between 1 / 90000 and 1 / 100000.
[0048] If at least one metal (M) is provided in step (a'), a suitable amount thereof is determined in order to obtain a molar ratio M / M+Ce of the metal (M)-doped cerium oxide particles produced according to this embodiment comprised between 0.01 and 0.15, more particularly between 0.01 and 0.12.
[0049] The metal (M), when present in the aqueous solution of step (a'), is provided by a salt which may be metal (M) nitrate, chloride, sulfate, phosphate, acetate or carbonate, as well as mixtures of these salts, such as mixed nitrates / chlorides. It is preferably a metal (M) nitrate. The metal (M) is as defined above in the description relating to step (a) of the method of the invention.
[0050] No.3 - The amount of nitrate ions in the aqueous solution used in step (a'), expressed by the molar ratio nitrate / Ce(III), is usually 1 / 3 to 5 / 1.
[0051] The acidity of the aqueous solution used in step (a') is chosen so that the cerium(III) is completely in solution. It is preferably comprised between 0.8N and 12.0N.
[0052] Cerium (IV) can be provided in step (a') by a salt which can be cerium (IV) nitrate, sulfate, ammonium cerium nitrate, ammonium cerium sulfate. It is preferably cerium (IV) nitrate. The cerium nitrate solution can be advantageously obtained by a method of electrochemical oxidation of a cerium nitrate solution as disclosed in French patent FR 2 570 087. The solution of cerium nitrate obtained according to the teachings of French patent FR 2 570 087 can exhibit an acidity of about 0.6N.
[0053] Cerium(III) may be provided in step (a') by a salt which may be cerium(III) nitrate, chloride, sulfate, phosphate, acetate or carbonate, as well as mixtures of these salts such as mixed nitrate / chloride. It is preferably cerium(III) nitrate.
[0054] The amount of free oxygen in the starting solution in step (a') should be carefully controlled and minimized. To this end, the starting solution may be degassed by bubbling with an inert gas. The term "inert gas" or "inert atmosphere" is intended to mean an atmosphere or gas that does not contain oxygen, the gas can be, for example, nitrogen or argon.
[0055] As base used in step (a') products of hydroxide type can in particular be used. Mention may be made of hydroxides of alkali metals or alkaline earth metals and aqueous ammonia. Secondary, tertiary or quaternary amines can also be used. The aqueous solution of the base can also be degassed beforehand by bubbling with an inert gas. The amount of base used in step (a'), expressed as the molar ratio base / (Ce + optional M), is preferably comprised between 8.0 and 30.0. This ratio may preferably be greater than 9.0.
[0056] Step (a') is usually carried out at a temperature comprised between 5°C and 50°C. This temperature may also be between 20 and 25°C.
[0057] Step (b') is the thermal treatment of the reaction medium obtained at the end of the previous step. It consists of (i) a heating substep and (ii) an ageing substep. The heating substep (i) consists of heating the medium at a temperature usually comprised between 75°C and 95°C, more particularly between 80°C and 90°C, and even more particularly between 85°C and 90°C.
[0058] The ageing substep (ii) consists in maintaining the medium at a temperature comprised between 75°C and 95°C, more particularly between 80°C and 90°C, even more particularly between 85°C and 90°C. The duration of the ageing substep (ii) is between 2 hours and 20 hours. The higher the temperature of the ageing step, the lower the time of the ageing substep. For example, when the temperature of the maturation substep is between 85°C and 90°C, for example 88°C, the duration of the maturation substep may be between 2 hours and 15 hours, more particularly between 4 hours and 15 hours. When the temperature of the maturation substep is between 75°C and 85°C, for example 80°C, the duration of the maturation substep may be between 15 hours and 30 hours.
[0059] During step (b'), oxidation of Ce(III) to Ce(IV) takes place. This step may be carried out under an inert atmosphere. The comments regarding the atmosphere for step (a') apply here.
[0060] In step (c'), the mixture obtained at the end of step (b') may be optionally acidified. This step (c') may be carried out by using nitric acid. The reaction mixture may be acidified with HNO3 to a pH lower than 3.0, more particularly comprised between 1.5 and 2.5.
[0061] In step (d'), the solid material obtained at the end of step (b') or step (c') is washed with water, preferably deionized water. This operation allows to reduce the amount of residual anions, especially nitrates, in the dispersion and to obtain the target conductivity. This step can be carried out by filtering the solid from the mixture and redispersing the solid in water. Filtration and redispersion can be carried out several times if necessary.
[0062] In step (e'), the solid material obtained at the end of step (d) can be subjected to a mechanical treatment to deagglomerate the particles. This step can be carried out by double jet processing or ultrasonic deagglomeration. This step usually results in a sharp particle size distribution and a reduction in the number of large agglomerated particles. According to one embodiment, the cerium-based particles have been subjected to a mechanical deagglomeration treatment. According to another embodiment, the cerium-based particles have not been subjected to a mechanical deagglomeration treatment.
[0063] After step (e'), the solid material can be dried to obtain the cerium-based particles provided in step (a) in powder form. After step (e'), water can also be added to directly obtain an aqueous dispersion of the cerium-based particles provided in step (a).
[0064] The aqueous solution provided in step (a) The purpose of the aqueous solution containing a cerium (III) salt, the aqueous peroxygen solution, and the optional aqueous solution containing at least one metal (M') salt is to form the shell nanoparticles of the cerium-based core-shell particles that are produced.
[0065] The cerium(III) salt may be cerium(III) nitrate, chloride, sulfate, phosphate or carbonate and also mixtures of these salts, such as mixed nitrates / chlorides. It is preferably cerium(III) nitrate.
[0066] Nitrate ions can be provided in either step (a) or (b). Molar ratio NO3 - The amount of nitrate ions, expressed as / Ce(III), is generally 1 / 3 to 5 / 1.
[0067] The acidity of the aqueous solution containing cerium (III) salt provided in step (a) is selected such that cerium (III) is completely in solution, which is preferably comprised between 0.8 N and 12.0 N. In that respect, suitable acids such as nitric acid, hydrochloric acid, sulfonic acid, carbonic acid, picolinic acid, propionic acid and mixtures thereof can be used, which is preferably nitric acid.
[0068] It is advantageous to use salts and ingredients of high purity. The purity of the salt may be at least 99.5% by weight, more particularly at least 99.9% by weight.
[0069] According to one embodiment in which it is desired to obtain a shell of metal (M')-doped cerium oxide, an aqueous solution comprising at least one metal (M') salt is also provided in step (a). The metal (M') salt may be metal (M') nitrate, chloride, sulfate, phosphate, acetate or carbonate, as well as mixtures of these salts, such as mixed nitrates / chlorides. It is preferably a metal (M') nitrate. When it is desired to produce cerium-based core-shell particles in which both the core and the shell are doped, the metal (M') may be identical or different to the metal (M) described above. The metal (M') may more particularly be selected from the group consisting of alkali metal elements, alkaline earth metal elements, rare earth elements, actinide elements, transition metal elements and post-transition metal elements from the periodic table. The definitions of these groups of elements shown in association with the metal (M) apply equally. Preferably, said at least one metal (M') is selected from the group consisting of transition metal elements such as Zr; post-transition metal elements such as Al; rare earth elements such as La, Pr, Nd and Y; and alkaline earth metal elements such as Sr. More preferably, said at least one metal (M') is selected from the group consisting of lanthanum, praseodymium, neodymium and zirconium. Even more preferably, said at least one metal (M') is selected from the group consisting of lanthanum, praseodymium and neodymium. Even more preferably, said at least one metal (M') is lanthanum.
[0070] According to this embodiment, the amount of salt of a metal (M') can be determined to obtain a molar ratio M' / M'+Ce in the shell of the core-shell particle comprised between 0.01 and 0.15, more particularly between 0.01 and 0.12.
[0071] In step (a), an aqueous solution of peroxygen is also provided. In the present invention, the peroxygen is Ce 3+ Ion to Ce 4+ It is used as an oxidizing agent to convert substances into ions.
[0072] The peroxygen used in the present invention can be selected from hydrogen peroxide, water-soluble peracids, and any other water-soluble molecule containing a peroxygen group of the formula -OO-. Hydrogen peroxide is preferred.
[0073] The amount of peroxygen in the aqueous peroxygen solution used may be in the range of 5 to 70% by weight, particularly 20 to 50% by weight, and more specifically 30 to 40% by weight, based on the total weight of the aqueous peroxygen solution.
[0074] Process (b) Step (b) consists in reacting, while maintaining a temperature comprised between 0° C. and 80° C. and a pH below 11, an aqueous dispersion comprising particles of cerium oxide optionally doped with at least one metal (M), an aqueous solution comprising a cerium (III) salt, an aqueous peroxygen solution, and an aqueous solution comprising at least one metal (M′) salt provided in optional step (a), to produce a dispersion of cerium-based core-shell particles.
[0075] The aqueous dispersion and the aqueous solution can be contacted simultaneously or sequentially, in any order, or in any combination.
[0076] In particular, an aqueous dispersion comprising particles of cerium oxide, optionally doped with at least one metal (M), may be contacted with an aqueous solution comprising a cerium (III) salt, and the resulting solution may be contacted with an aqueous peroxygen solution.
[0077] When both are provided, the aqueous solution comprising a cerium (III) salt and the aqueous solution comprising at least one metal (M') salt can in particular be contacted with each other prior to step (b) to form an aqueous solution comprising a cerium (III) salt and at least one metal (M') salt. A dispersion comprising particles of cerium oxide, optionally doped with at least one metal (M), can be contacted with this solution. The resulting solution can then be contacted with an aqueous peroxygen solution.
[0078] The contacting step (b) may comprise a contacting substep (i) followed by an ageing substep (ii). During the contacting substep (i), the dispersion and the solution are brought into contact with each other while maintaining the required temperature and pH. During the ageing substep (ii), the medium resulting from the contacting substep (i) is maintained at the required temperature and pH for a specific time.
[0079] The contacting substep (i) may be carried out by introducing the solution into the dispersion provided in step (a), preferably gradually and / or sequentially.
[0080] The molar ratio of cerium oxide / cerium(III) before starting step (b) may be comprised between 1 / 1 and 100 / 1, in particular between 3 / 1 and 30 / 1, and more particularly between 5 / 1 and 15 / 1.
[0081] The molar ratio of peroxygen / cerium(III) before starting step (b) is preferably less than 0.50, in particular less than or equal to 0.40, more particularly less than or equal to 0.38. It is preferably greater than or equal to 0.01, in particular greater than or equal to 0.10, more particularly greater than or equal to 0.20.
[0082] The duration of the ageing substep (ii) may be between 2 hours and 24 hours, in particular between 2 hours and 10 hours, more particularly between 2 hours and 5 hours.
[0083] The temperature of the medium is maintained during the time of step (b) at a value comprised between 0° C. and 80° C., preferably between 10° C. and 60° C., more preferably between 15° C. and 45° C., in particular between 20° C. and 40° C., more particularly between 25° C. and 35° C., even more particularly between 30° C. and 35° C. Very noteworthy, the process can be operated at lower temperatures. Energy savings can therefore be achieved.
[0084] The pH of the medium is maintained at a value below 11, preferably between 3 and 11, preferably between 4 and 11, preferably between 8 and 11, more preferably between 8 and 10, especially between 8 and 9, more particularly about 8, during the time of step (b). Depending on the initial pH of the medium, the pH adjuster can be an acid or a base. Suitable acids include nitric acid, hydrochloric acid, sulfonic acid, carbonic acid, picolinic acid, propionic acid, and mixtures thereof, preferably nitric acid. Suitable bases include alkali metal and alkaline earth metal hydroxides and aqueous ammonia. Secondary, tertiary or quaternary amines can also be used. Aqueous ammonia is preferred. According to a preferred embodiment, the pH adjuster is a base, preferably aqueous ammonia.
[0085] Step (b) may advantageously be carried out at atmospheric pressure (i.e. at about 1,013.25 mbar).
[0086] Step (b) may be carried out in an inert or non-inert atmosphere. The term "inert atmosphere" has the same meaning as explained above. According to one embodiment, the reaction is carried out in an oxidizing atmosphere. "Oxidizing atmosphere" has its usual meaning for the skilled person, i.e. an atmosphere containing free oxygen. It may be air or any oxygen-containing atmosphere, such as, for example, a molecular oxygen-rich atmosphere.
[0087] Agitation of the medium may be performed during the time of step (b).
[0088] According to one embodiment, no Ce(IV) salt is introduced in either step (a) or (b). In conventional cerium precipitation-based methods, cerium(IV) ions are used as crystal seeds to promote nucleation in solution. However, in the method of the present invention, the cerium-based particles provided from the dispersion of step (a) and intended to be core particles already fulfill this role. The presence of additional Ce(IV) salts may lead to the formation of small cerium oxide particles independent of the core-shell particles, thus increasing the dispersion index of the resulting particle dispersion, which is undesirable for the targeted polishing application.
[0089] Optional step (c) In step (c), the mixture obtained at the end of step (b) or step (d) detailed below may be optionally acidified. This step (c) may be carried out using a suitable acid such as nitric acid, picolinic acid, propionic acid, hydrochloric acid, sulfonic acid, carbonic acid, and mixtures thereof, preferably nitric acid. The reaction mixture may be acidified to a pH below 3.0, more particularly comprised between 1.5 and 2.5.
[0090] Optional Step (d) In step (d), the solid material obtained at the end of step (b) or step (c) can be washed with water, preferably deionized water. When both are performed, steps (c) and (d) can be performed in any order. This operation reduces the amount of residual anions, especially nitrates, in the dispersion and allows the target conductivity to be obtained. This step can be performed by filtering the solid from the mixture and redispersing the solid in water. Filtration and redispersion can be performed several times if necessary.
[0091] Optional step (e) In step (e), the solid material obtained at the end of steps (b), (c) or (d) can be subjected to a mechanical treatment to deagglomerate the core-shell particles. This step can be carried out by double jet processing or ultrasonic deagglomeration. This step usually results in a sharp particle size distribution and a reduction in the number of large agglomerated particles. According to one embodiment, the cerium-based core-shell particles are subjected to a mechanical treatment of deagglomeration. According to another embodiment, the cerium-based core-shell particles are not subjected to a mechanical treatment of deagglomeration.
[0092] After step (e), the solid material can be dried in step (f) to obtain the cerium-based core-shell particles of the invention in powder form. After step (e), water can also be added to obtain an aqueous dispersion of the cerium-based core-shell particles according to the invention. Liquids other than water can be used to prepare the dispersion according to the invention, such as water / water-miscible, compatible solvent mixtures or organic solvents. Such dispersions can be prepared from the aqueous dispersion obtained by the process of the invention by methods known per se. The pH of the dispersion can also be adjusted to a value typically between 4 and 6.
[0093] According to one embodiment, cerium-based core-shell particles are produced having a cerium oxide core and a shell consisting of La-doped cerium oxide nanoparticles, for which, to carry out the method as described above, an aqueous dispersion of cerium oxide particles, an aqueous solution comprising a cerium(III) salt, preferably cerium(III) nitrate, and an aqueous solution comprising a lanthanum salt, preferably lanthanum nitrate, are provided in step (a).
[0094] According to another embodiment, cerium oxide core-shell particles having a cerium oxide core and a shell consisting of cerium oxide nanoparticles are produced, for which purpose, in order to carry out the method as described above, an aqueous dispersion of cerium oxide particles and an aqueous solution comprising a cerium(III) salt, preferably cerium(III) nitrate, are provided in step (a).
[0095] particle The present invention relates to cerium-based core-shell particles obtainable or obtained by the process described above.
[0096] The present invention particularly relates to cerium-based core-shell particles, each cerium-based core-shell particle having a core particle made of cerium oxide optionally doped with at least one metal (M) and a shell consisting of a plurality of nanoparticles of cerium oxide optionally doped with at least one metal (M'), said nanoparticles being formed on the surface of the core particle, and wherein the ratio of the average particle size of the core-shell particles measured by TEM to the average particle size of the core-shell particles measured by BET is at least 1.5.
[0097] Such cerium-based core-shell particles may further exhibit: - an average core-shell particle size, measured by TEM, of at most 200 nm, in particular at most 190 nm; it may also be at most 180 nm, in particular at most 150 nm, at most 140 nm, at most 130 nm or even at most 120 nm. The cerium oxide particles may exhibit an average particle size, measured by TEM, of at least 30 nm, in particular at least 40 nm, more particularly at least 50 nm. The standard deviation of the value of said average particle size may be at most 30%, in particular at most 25%, in particular at most 20%, more particularly at most 15%; and / or - an average core-shell particle size, calculated from BET surface measurement, of at most 120 nm, in particular at most 100 nm, in particular at most 85 nm. The cerium oxide particles may exhibit an average particle size, calculated from BET surface measurement, of at least 15 nm, in particular at least 19 nm, in particular at least 20 nm, in particular at least 30 nm; and / or - the ratio of the average particle size of the core-shell particles, as determined by TEM, to the average particle size of the core-shell particles, as determined by BET, is in particular at least 1.7, at least 1.9, more in particular at least 2.0; and / or a hydrodynamic mean diameter Dh, determined by DLS, comprised between 50 nm and 300 nm, in particular between 70 nm and 280 nm, in particular between 80 nm and 250 nm, in particular between 90 nm and 230 nm. a median diameter D50, determined from a distribution obtained by laser diffraction, comprised between 30 nm and 180 nm, in particular between 60 nm and 160 nm, more particularly between 80 nm and 150 nm, and even more particularly between 90 nm and 145 nm; and / or a median diameter D10 determined from a distribution obtained by laser diffraction and falling within the range of 10 nm to 160 nm, in particular 40 nm to 130 nm, more particularly 60 nm to 120 nm, and even more particularly 70 nm to 110 nm; and / or a median diameter D90 determined from a distribution obtained by laser diffraction, comprised between 45 nm and 250 nm, in particular between 90 nm and 220 nm, more particularly between 100 nm and 210 nm, and even more particularly between 110 nm and 200 nm; and / or a dispersion index of at most 0.5, in particular at most 0.4, at most 0.3, determined from a distribution obtained by laser diffraction; and / or - the ratio of the average particle size of the nanoparticles from the shell, measured by TEM, to the average particle size of the core particles, measured by TEM, is at most 1 / 2, in particular at most 1 / 3, in particular at most 1 / 4; and / or - 8-60m, determined by BET 2 / g, especially 8-45m 2 / g, especially 8-30m 2 / g, especially 10~28m 2 / g, especially 14~25m 2 / g, more specifically 15-22m 2 / g specific surface area; and / or - average crystallite size comprised between 60 and 120 nm, in particular between 60 and 80 nm. It is calculated from the FWHM of the (111) plane by applying the Scherrer model with the Scherrer constant equal to 0.94.
[0098] In the embodiment of the present patent application, the minimum value of D10, D50, and D90 may be selected, respectively. In the embodiment of the present patent application, the maximum value of D10, D50, and D90 may be selected, respectively.
[0099] The metals (M) and / or (M') optionally present in the core-shell particles of the invention may be chosen among the metals described above in connection with the manufacturing process.
[0100] When the core particle is doped with at least one metal (M), the molar ratio M / M+Ce in the core particle may be comprised between 0.01 and 0.15, more particularly between 0.01 and 0.13, in particular between 0.01 and 0.12.
[0101] When the shell nanoparticles are doped with at least one metal (M'), the molar ratio M' / M'+Ce in the shell particle may be comprised between 0.01 and 0.15, more particularly between 0.01 and 0.13, in particular between 0.01 and 0.12.
[0102] According to a particular embodiment of the invention: - both the core and shell particles are made from cerium oxide; or - the core particles are made of cerium oxide and the shell particles are made of lanthanum-doped cerium oxide; or - the core particles are made of lanthanum doped cerium oxide and the shell particles are made of cerium oxide; or The core particles are made from lanthanum doped cerium oxide and the shell particles are made from lanthanum doped cerium oxide.
[0103] dispersion liquid The present invention also relates to a dispersion of the cerium-based core-shell particles of the present invention in a liquid medium.
[0104] The zeta potential of the cerium-based core-shell particles contained in the dispersion of the invention is advantageously positive. It can be measured at a pH value of the dispersion comprised between 4 and 9.5. The zeta potential can be measured with a zetameter DT300 from Quantachrome for a 1% by weight dispersion.
[0105] The dispersions of the present invention may advantageously exhibit a conductivity of less than 600 μS / cm, less than 300 μS / cm, more particularly less than 150 μS / cm, and even more particularly less than 100 μS / cm.
[0106] The liquid medium may be water or a mixture of water and a water-miscible organic liquid. The water-miscible organic liquid should not cause the particles to precipitate or aggregate. The water-miscible organic liquid may be, for example, an alcohol such as isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol; a ketone such as acetone, diacetone alcohol, methyl ethyl ketone; or an ester such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate. The ratio of water / organic liquid may be 80 / 20 to 99 / 1 (wt / wt).
[0107] The proportion of cerium-based core-shell particles in the dispersion may be comprised between 0.5% and 40.0% by weight, this proportion being expressed as the weight of cerium-based core-shell particles relative to the total weight of the dispersion, and this ratio may be comprised between 10.0% and 35.0% by weight.
[0108] Use of cerium-based core-shell particles or dispersions The cerium-based core-shell particles of the present invention or the dispersion of the present invention can be used to prepare polishing compositions, more particularly CMP compositions. They are used as components of polishing compositions, more particularly CMP compositions.
[0109] CMP compositions (or chemical-mechanical polishing compositions) are polishing compositions used to selectively remove material from the surface of a substrate. They are used in the field of integrated circuits and other electronic devices. In fact, in the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive and dielectric materials are deposited on or removed from the surface of a substrate. As layers of material are sequentially deposited on and removed from the substrate, the top surface of the substrate may become non-planar and require planarization. Planarization of a surface (or "polishing" a surface) is the process of removing material from the surface of a substrate to form a generally smooth and flat surface. Planarization is useful for removing undesirable surface topography and surface defects, such as rough surfaces, agglomerated materials, crystal lattice damage, scratches and contaminated layers or materials. Planarization is also useful for forming features on a substrate by removing excess deposited material that was used to fill the features and provide a smooth surface for subsequent levels of metallization and processing.
[0110] The substrate that can be polished with the polishing or CMP composition can be, for example, a silicon dioxide type substrate, glass, semiconductor, or wafer.
[0111] The polishing composition or CMP composition typically contains different components other than the cerium-based core-shell particles. The polishing composition may include one or more of the following components: - abrasive particles other than cerium-based particles (referred to herein as "additional abrasive particles"); and / or - pH adjusters; and / or - surfactants; and / or - rheology control agents, including viscosity enhancers and coagulants; and / or - anionic copolymers of carboxylic, sulfonated or phosphonated monomers with acrylates, polyvinylpyrrolidones or polyvinyl alcohols (e.g. copolymers of 2-hydroxyethyl methacrylate and methacrylic acid); non-ionic polymers which are polyvinylpyrrolidones or polyethylene glycols; silanes which are aminosilanes, ureidosilanes or glycidylsilanes; functionalized N-oxides of pyridines (e.g. picolinic acid N-oxide); starch; cyclodextrins (e.g. α-cyclodextrin or β-cyclodextrin); and combinations thereof.
[0112] The pH of the polishing composition is generally within the range of 1 to 6. Typically, the polishing composition has a pH of 3.0 or higher. Also, the pH of the polishing composition is typically 6.0 or lower.
[0113] The cerium-based core-shell particles of the present invention can be used in the polishing compositions disclosed in the following documents: WO 2013 / 067696; WO 2016 / 140968; WO 2016 / 141259; WO 2016 / 141260; WO 2016 / 047725; WO 2016 / 006553.
[0114] The present invention also relates to a method for removing a portion of a substrate comprising polishing the substrate with a polishing composition prepared from a dispersion containing cerium-based core-shell particles according to the present invention.
[0115] The invention finally relates to a semiconductor containing substrate polished by this method.
[0116] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control. EXAMPLES
[0117] The present invention is further illustrated in the following examples, which are not intended to limit the invention.
[0118] Example 1: Particles with Core CeO2 and Shell CeO2 - Concentration 20 wt% A 20 wt% aqueous dispersion of cerium oxide particles is prepared by adding 895.7 g of 31.3 wt% aqueous CeO2 dispersion Zenus® (average primary particle size calculated by BET measurements = 60 nm) commercially available from Solvay to 504.3 g of deionized water. A dilute ammonia solution is prepared by adding 135.1 g of 28% aqueous ammonia to 664.9 g of deionized water. A solution of cerium nitrate is prepared by adding 153.4 g of 2.87 M cerium nitrate solution to 21.2 g of deionized water.
[0119] A 20% by weight aqueous cerium oxide dispersion is introduced into a 2 L semi-closed jacketed reactor and then stirred (stirrer with 4 pitched blades at 600 rpm). The reaction mixture is then heated to 35° C. under the same stirring. The initial pH of the dispersion is increased to 8 by adding a 2.5 M ammonia solution. A trivalent cerium nitrate solution is then added at 7 g / min by a peristaltic pump. During this process, the pH is maintained at 8 by controlled addition of a 2.5 M ammonia solution. After the addition is over, the reaction mixture is maintained at the same temperature and stirring for 3 minutes, then 10.74 g of a commercial 30.9% by weight H2O2 solution is added in 6 minutes. The reaction mixture is then maintained at the same temperature and stirring for 2 hours 47 minutes. Over this time, the pH is maintained by controlled addition of ammonia solution at 2.5 M. The reaction is then stopped and the dispersion is washed several times by centrifugation, the centrifugation supernatant is removed and the cake is redispersed in deionized water. Finally, the dispersion was adjusted to 10-15% by weight, with a pH of about 5 and an ionic conductivity of 0.1 mS.cm -1 The dispersion is deagglomerated by successive passage through a dual impact jet homogenizer.
[0120] The obtained dispersion is observed by TEM (Figure 1). It is observed that the cerium salt precipitates on the doped cerium oxide particles, forming a shell with a rough surface. The average particle size is determined after counting 150 particles on the TEM image, giving an average particle size of 109 nm.
[0121] A portion of the dispersion is dried in an oven at 200° C., which gives a powder for the measurement of the BET surface area. The BET specific surface area, determined by nitrogen adsorption, is 13 m for the starting particles. 2 / g and 20m for core-shell particles. 2 / g, resulting in average primary particle sizes of 64 nm and 42 nm, respectively (giving a ratio of average size TEM / size BET 2.6). The secondary particle size is also measured by dynamic light scattering (DLS) at a relative refractive index of 1.7 for CeO2 in water. The hydrodynamic diameter is 158 nm for the core-shell particles.
[0122] Example 2: Particles with lanthanum doped cerium oxide core and cerium oxide shell Prepare an aqueous dispersion of 20 wt% lanthanum-doped cerium oxide particles by adding 940.5 g of a 29.8 wt% CeO2:La aqueous dispersion (average primary particle size calculated from BET measurements = 74 nm, La / La+Ce molar ratio of 0.025, synthesized according to Example 1 of WO 2018 / 229005) into 459.5 g of deionized water. Prepare a dilute ammonia solution by adding 132.7 g of 28% aqueous ammonia into 667.3 g of deionized water. Prepare a solution of cerium nitrate by adding 70.5 g of 2.87 M cerium nitrate solution into 41.3 g of deionized water.
[0123] A 20% by weight aqueous cerium oxide dispersion is introduced into a 2 L semi-closed jacketed reactor and then stirred (stirrer with 4 pitched blades at 600 rpm). The reaction mixture is then heated to 35° C. under the same stirring. The initial pH of the dispersion is increased to 8 by adding a 2.5 M ammonia solution. A trivalent cerium nitrate solution is then added at 3.2 g / min by a peristaltic pump. During this process, the pH is maintained at 8 by controlled addition of a 2.5 M ammonia solution. After the addition is over, the reaction mixture is maintained at the same temperature and stirring for 3 minutes, then 4.88 g of a commercial 30.9% by weight H2O2 solution is added in 3 minutes 20 seconds. The reaction mixture is then maintained at the same temperature and stirring for 2 hours 46 minutes. Over this time, the pH is maintained by controlled addition of ammonia solution at 2.5 M. The reaction is then stopped and the dispersion is washed several times by centrifugation, the centrifugation supernatant is removed and the cake is redispersed in deionized water. Finally, the dispersion is adjusted to 10-15% by weight, with a pH of about 5 and an ionic conductivity of less than 0.1 mS.cm-1. The dispersion is deagglomerated by successively passing it through a dual impact jet homogenizer.
[0124] The obtained dispersion is observed by TEM (Figure 3). It is observed that the cerium salt precipitates on the doped cerium oxide particles, forming a shell with a rough surface. The average particle size is determined after counting 150 particles on the TEM image, giving an average particle size of 137 nm.
[0125] A portion of the dispersion is dried in an oven at 200° C., which gives a powder for the measurement of the BET surface area. The BET specific surface area, determined by nitrogen adsorption, is 11.3 m for the starting particles. 2 / g and 12.9m for core-shell particles. 2 / g, resulting in average primary particle sizes of 74 nm and 65 nm, respectively (giving a ratio of average size TEM / size BET 2.1). The secondary particle size is also measured by dynamic light scattering (DLS) at a relative refractive index of 1.7 for CeO2 in water. The hydrodynamic diameter is 200 nm for the core-shell particles.
[0126] Example 3: Particles with a cerium oxide core and a lanthanum-doped cerium oxide shell A 5 wt.% aqueous dispersion of cerium oxide particles is prepared by adding 246.7 g of a 28.4 wt.% aqueous dispersion of CeO2 Zenus® (average primary particle size calculated by BET measurements = 60 nm) commercially available from Solvay to 1153.3 g of deionized water. A dilute ammonia solution is prepared by adding 132.7 g of 28% aqueous ammonia to 667.3 g of deionized water. A 2.87 mol / L CeO2 dispersion in 87.5 g of deionized water is prepared by adding 132.7 g of 28% aqueous ammonia to 667.3 g of deionized water. 3+ 22.8g of trivalent cerium nitrate solution and 2.87mol / L of La 3+ A solution of trivalent cerium nitrate and lanthanum nitrate is prepared by adding 2.6 g of lanthanum nitrate solution.
[0127] A 5% by weight aqueous cerium oxide dispersion is introduced into a 2 L semi-closed jacketed reactor and then stirred (stirrer with 4 pitched blades at 600 rpm). The reaction mixture is then heated to 35° C. under the same stirring. The initial pH of the dispersion is increased to 8 by adding a 2.5 M ammonia solution. The trivalent cerium nitrate solution and the lanthanum nitrate solution are then added at 4.2 g / min by a peristaltic pump. During this process, the pH is maintained at 8 by the controlled addition of a 2.5 M ammonia solution. After the addition is over, the reaction mixture is maintained at the same temperature and with the same stirring for 3 minutes, then 1.58 g of a commercial 30.9% by weight H2O2 solution is added in 3 minutes 20 seconds. The reaction mixture is then maintained at the same temperature and with stirring for 2 hours 23 minutes. Over this time the pH is maintained by the controlled addition of ammonia solution at 2.5 M. The reaction is then stopped and the dispersion is washed several times by centrifugation, the centrifugation supernatant is removed and the cake is redispersed in deionized water. Finally, the dispersion was adjusted to 10-15% by weight, with a pH of about 5 and an ionic conductivity of 0.1 mS.cm -1 The dispersion is deagglomerated by successive passage through a dual impact jet homogenizer.
[0128] The obtained dispersion is observed by TEM (Figure 4). It is observed that the cerium salt precipitates on the doped cerium oxide particles, forming a shell with a rough surface. The average particle size is determined after counting 150 particles on the TEM image, giving an average particle size of 109 nm.
[0129] A portion of the dispersion is dried in an oven at 200° C., thereby obtaining a powder for the measurement of the BET surface area. The BET specific surface area, determined by nitrogen adsorption, is 13 m for the starting particles. 2 / g and 16.7m for core-shell particles. 2 / g, resulting in average primary particle sizes of 64 nm and 50 nm, respectively (giving a ratio of average size TEM / size BET 2.2). The secondary particle size is also measured by dynamic light scattering (DLS) at a relative refractive index of 1.7 for CeO2 in water. The hydrodynamic diameter is 154 nm for the core-shell particles.
[0130] Comparative Example 1: Example 1 is repeated, except that the temperature applied is 85° C. instead of 35° C. The dispersion is observed by TEM. It is noted that the starting particles are not covered by small crystallites (no core-shell structure).
[0131] Comparative Example 2: Example 1 is repeated, except that the pH is 12 instead of 8. The dispersion is observed by TEM. It is noted that the starting particles are aggregated and are not covered by small crystallites (no core-shell structure).
[0132] Comparative example 3: Hydrothermal synthesis A 5 wt% aqueous dispersion of cerium oxide particles is prepared by adding 41.6 g of 30 wt% aqueous cerium oxide dispersion Zenus® (average primary particle size calculated by BET measurements = 60 nm) commercially available from Solvay to 208.4 g of deionized water. A 1 N ammonia solution is prepared by adding 28 g of 28% aqueous ammonia to 771 g of deionized water. A solution of cerium nitrate is prepared by adding 0.75 g of 2.87 M trivalent cerium nitrate solution to 249.25 g of deionized water.
[0133] A 5% by weight suspension of cerium oxide and a trivalent cerium nitrate solution are introduced into a 2 L semi-closed jacketed reactor and then stirred (stirrer with 4 pitched blades at 300 rpm). The pH of the mixture is adjusted to 11 by the addition of an appropriate amount of 1N ammonia solution and stirred for 2 hours. The solution is then transferred to a Teflon bottle and placed in a stainless steel autoclave at 170 °C for 12 hours. The dispersion is observed by TEM (Figure 3). It is noted that the starting particles are not covered by small crystallites (there is no core-shell structure).
[0134] Evaluation of polishing performance The polishing machine used is a Struers Tegramin. The surfaces to be polished are made of amorphous silica. The aqueous dispersions of core-shell particles were tested under the following conditions: Head pressure: 50N Rotation speed: 150 rpm; · Padding: Neoprene (MD-Chem) - new pads per order; Dispersion flow rate: 15mL / min; Dispersion: The amount of core-shell particles is 1% by weight; · The pH of the dispersion is comprised between 6.0 and 6.1 and is obtained by adding dilute NH4OH; Polishing time: 10 minutes.
[0135] As a reference, an aqueous dispersion of cerium oxide of Zenus® particles (average CeO2 primary particle size calculated by BET measurements = 60 nm) commercially available from Solvay is used at 1% by weight and pH = 6.0.
[0136] The polishing procedure is as follows: 1) testing a reference dispersion; 2) testing the sample; 3) Test the sample a second time. Between each step of the procedure, the pad is cleaned with deionized water and the dispersion to be tested is introduced under a controlled flow rate onto the surface to be polished.
[0137] The weight loss of the substrate is recorded. The removal rate (RR) expressed in nm / min is then calculated as follows:
number
[0138] The removal efficiency ratio is the ratio of the average removal achieved with the dispersions tested for each sequence to the removal achieved with the reference dispersion, which is 1.28 for the particles of Example 1 and 1.38 for the particles of Example 2, reflecting an improvement in removal compared to the references used (removal efficiency ratios greater than 1).
[0139] At the end of the polishing test, the substrate and the core-shell particles are visually inspected: it is confirmed that the nanoparticles from the shell of the core-shell particles of the invention are sufficiently immobilized and have remained attached to the core during polishing.
Claims
1. 1. A method for producing a dispersion of cerium-based core-shell particles in a liquid, comprising: (a) providing an aqueous dispersion comprising particles of cerium oxide optionally doped with at least one metal (M); providing an aqueous solution comprising a cerium (III) salt; providing an aqueous peroxygen solution; and optionally providing an aqueous solution comprising at least one metal (M') salt; (b) contacting said aqueous dispersion with said aqueous solution provided in step (a) while maintaining a temperature comprised between 0° C. and 80° C. and a pH of less than or equal to 11 to produce a dispersion of cerium-based core-shell particles; wherein at least one of steps (a) and (b) is carried out in the presence of nitrate ions.
2. 2. The method according to claim 1, wherein the aqueous dispersion in step (a) comprises at least 3% by weight, in particular at least 5% by weight, in particular at least 10% by weight, in particular at least 15% by weight and more particularly at least 20% by weight of particles of cerium oxide optionally doped with at least one metal (M) relative to the total weight of the aqueous dispersion.
3. 3. The method of claim 1 or 2, wherein the particles provided in the aqueous dispersion in step (a) are particles of cerium oxide.
4. 3. The method according to claim 1 or 2, wherein the particles provided in the aqueous dispersion in step (a) are particles of cerium oxide doped with at least one metal (M) selected from the group consisting of alkali metal elements, alkaline earth metal elements, rare earth elements, actinide elements, transition metal elements and post-transition metal elements from the periodic table.
5. 5. The method of claim 4, wherein the metal (M) is selected from the group consisting of Zr, Al, La, Pr, Nd, Y, and Sr.
6. 5. The process according to claim 4, wherein the molar ratio M / (M+Ce) of said particles provided in said aqueous dispersion in step (a) is comprised between 0.01 and 0.15, preferably between 0.01 and 0.
12.
7. 3. The method of claim 1 or 2, wherein the aqueous peroxygen solution provided in step (a) is a solution of hydrogen peroxide.
8. 3. The method according to claim 1 or 2, wherein the aqueous solution comprising the at least one salt of a metal (M') is provided in step (a), and the metal (M') is selected from the group consisting of alkali metal elements, alkaline earth metal elements, rare earth elements, actinide elements, transition metal elements and post-transition metal elements from the periodic table.
9. 9. The method of claim 8, wherein the metal (M') is selected from the group consisting of Zr, Al, La, Pr, Nd, Y, and Sr.
10. The method according to claim 8, wherein the shell molar ratio M' / (M'+Ce) of the produced core-shell particles is comprised between 0.01 and 0.15, preferably between 0.01 and 0.
12.
11. 3. The method according to claim 1 or 2, wherein the temperature in step (b) is maintained at from 10°C to 60°C, more preferably from 15°C to 45°C, in particular from 20°C to 40°C, more particularly from 25°C to 35°C, even more particularly from 30°C to 35°C.
12. 3. The method according to claim 1 or 2, wherein the pH in step (b) is maintained at 3 to 11, in particular 4 to 11, in particular 8 to 11, in particular 8 to 10, more particularly 8 to 9.
13. 3. The process according to claim 1 or 2, wherein the molar ratio of cerium oxide / cerium(III) before starting step (b) is comprised between 1 / 1 and 100 / 1, preferably between 3 / 1 and 30 / 1, preferably between 5 / 1 and 15 / 1.
14. The method of claim 1 or 2, further comprising, in any order, a step (c) of acidifying said dispersion of cerium-based core-shell particles and / or a step (d) of washing.
15. The method according to claim 1 or 2, further comprising a step (e) of deagglomeration of the cerium-based core-shell particles.
16. 10. The method of claim 1, further comprising the step (f) of drying the cerium-based core-shell particles.
17. 10. A dispersion of cerium-based core-shell particles in a liquid obtainable by the method of claim 1, each cerium-based core-shell particle having a core particle made of cerium oxide optionally doped with at least one metal (M) and a shell consisting of a plurality of nanoparticles of cerium oxide optionally doped with at least one metal (M'), said nanoparticles being formed on the surface of said core particles, and wherein the ratio of the average particle size of said core-shell particles measured by TEM to the average particle size of said core-shell particles measured by BET is at least 1.
5.
18. 17. A powder of cerium-based core-shell particles obtainable by the method according to claim 16, each cerium-based core-shell particle having a core particle made of cerium oxide optionally doped with at least one metal (M) and a shell consisting of a plurality of nanoparticles of cerium oxide optionally doped with at least one metal (M'), said nanoparticles being formed on the surface of said core particles, and wherein the ratio of the average particle size of said core-shell particles measured by TEM to the average particle size of said core-shell particles measured by BET is at least 1.
5.
19. 19. A polishing composition comprising the dispersion of the cerium-based core-shell particles according to claim 17 or the cerium-based core-shell particles according to claim 18.
20. Use of the cerium-based core-shell particle dispersion according to claim 17 or the cerium-based core-shell particle powder according to claim 18 for the preparation of a polishing composition, more particularly a chemical-mechanical polishing composition.
21. 20. A method for removing a portion of a substrate, comprising polishing the substrate with a polishing composition prepared from the dispersion of claim 16 or from a dispersion prepared from the core-shell cerium oxide particle powder of claim 18.
22. 22. A semiconductor comprising a substrate polished by the method of claim 21.